Grover Cleveland, again! : a treasury of American presidents - Burns, Ken, 1953-; Kelley, Gerald (New York : Knopf Books for Young Readers, 2016)
A treasury of American Presidents by historian Ken Burns.
Keywords: Presidents -- United States -- History -- Juvenile literature; Presidents -- United States -- Biography -- Juvenile literature; Biographies; Juvenile books